2024
DOI: 10.15407/economyukr.2021.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Провали Державного Регулювання На Ринку Праці Та Можливості Їх Мінімізації

Abstract: International cooperation, the development of the digital economy, and market globalization including the labor market became the reason for the production distribution and the transformation of the sector of employment. The national labor market is under the influence of combined tendencies, which result in diverging effects for its institutional entities. The state meets a number of problems, those restrain the formation of the labor market, which can meet modern economic needs and social challenges. The fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…аналіз останніх досліджень і публікацій Засади та результати оцінки втрат і збитків, завданих економіці та спільноті в ході збройних протистоянь, на різних етапах світової історії широко висвітлювалися в наукових джерелах, розробках профільних державних і громадських інституцій. У новітньому історичному періоді їх основу складають насамперед дослідження з національної безпеки, сталого розвитку, резильєнтності спектру сфер життєдіяльності країн і територіальних громад, маркетингу і менеджменту підприємства, ризикології [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: постановка проблемиunclassified
“…аналіз останніх досліджень і публікацій Засади та результати оцінки втрат і збитків, завданих економіці та спільноті в ході збройних протистоянь, на різних етапах світової історії широко висвітлювалися в наукових джерелах, розробках профільних державних і громадських інституцій. У новітньому історичному періоді їх основу складають насамперед дослідження з національної безпеки, сталого розвитку, резильєнтності спектру сфер життєдіяльності країн і територіальних громад, маркетингу і менеджменту підприємства, ризикології [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: постановка проблемиunclassified
“…Blyzniuk, et al [2] indicated the inconsistency of the volumes, directions, and quality of specialist training with the structure of demand for qualified labor. The reasons for this are the insufficient attention of institutional structures to the effects of: changes in the sectoral structure of the economy, reduction in the share of heavy industry, changes in the age structure of the workforce due to a sharp decrease in the share of youth, migration on the labor potential of the country.…”
mentioning
confidence: 99%